PENGUATAN KEMAMPUAN LITERASI DAN NUMERASI DALAM PRAKTIK PEMBELAJARAN BAGI PENDIDIK PAUD BERBASIS PESANTREN - Rohmah, Naili; Renistiara Medilianasari; Sugiana; Sri Sularti Dewanti Handayani; Nikmatuurohmah; Laila Zahwa Fi’atunnajiha; Kinanthi Wahyu Prastuti (LPPM UNINUS, 2024)
Early childhood education (PAUD) has become an inseparable part of the education unit. Nowadays, many PAUD units are established, have permits, and carry out accreditation. Meanwhile, there are still many educators in PAUD units whose education is not linear. This has an impact on the learning practices given to children being of lower quality, especially for PAUD which has an Islamic boarding school base which will be the choice of parents who hope that their children will receive general knowledge and religious knowledge facilities. The activity method used refers to five stages, namely preparation, training & education, experience, mentoring and monitoring. The service activities carried out include training Islamic boarding school-based PAUD educators in carrying out learning practices according to PAUD learning principles. Furthermore, partners receive strengthening in two areas, namely literacy and numeracy. Literacy skills by introducing receptive, expressive language and literacy. Numeracy ability by optimizing 8 branches of numeracy in early childhood. The eight branches of mathematics introduced are matching, classification, sorting, geometry, patterns, counting, data, and measurement. Based on the service activities carried out, it can be concluded that the service activities that have been carried out have had a positive impact on partners. Partners receive literacy and numeracy reinforcement during activities, and continue good practices by applying the literacy and numeracy material they have obtained during training activities